Pembuatan Dan Karakterisasi Ekstrak Kering Daun Sirih Hijau (Piper Betle L.) - Harrizul Rivai; Putri Eka Nanda; Humaira Fadhilah (Jurnal Farmasi Higea, 2014)
A study about production and characterization of dried Piper betle L. Leaf extracts with the a ddition of lactose as drying agents has been perfomed with various ratio 1:1, 1:1½ and 1:2. Ekstrak mode better various ratio 1:2 with dried extracts characterization result are : powder, fawn color.odor like plant and somewhat bitter taste. The dry extractswas madebycomparison ofextracts: lactose 1:1, 1:1½ and 1:2 and the best ekstract was in ratio 1:2, levels ofwater-soluble compounds extract 1:2 is 23.0699% ± 1.6353, levels ofethanolsolublecompounds 3.8094%  ±0.2109%, losses on drying 2.1367% ± 0.0144%, moisture content 2.0196 % ± 0.0019 %,apparentspecific gravity 0.5482 g/mL ± 0.0003 %, specific gravity of incompressible 0.5558 g/mL ± 0.0004 g/mL, The total ash content of 0.5660% ± 0.0613% and acidinsolubleash content of  0.5179%  ± 0.0309%.